A STUDY ON HELMINTH PARASITES OF BUFFALOES BROUGHT TO AHMEDABAD SLAUGHTER HOUSE, GUJARAT, INDIA: Life Sciences-Veterinary Parasitology - PATEL, H. C.; HASNANI, J.J; PATEL, P.V; PANDYA, S.S; SOLANKI, J, B; JADAV, S.J (International Journal of Life Science and Pharma Research, 2022)
Based on this study, the general prevalence rate of helminth parasites in buffaloes was found to be 64.67% on screening of 150 samples viz. faecal sample, affected tissues, abomasal content and other samples as per necropsy lesions. On class wise analysis it was revealed that 64 % cases are of trematodes, followed by nematodes and cestodes with 26% and 10% infection, respectively. On species wise analysis, it was found that the prevalence of Fasciola gigantica was the highest (15.33%) and that of Moniezia benedeni was the least (2.66%) among eight observed species. On quantitative examination of faecal samples, it was revealed that the egg counts for all observed species were ranged between 100 to 1400; with a maximum count for F. gigantca and lowest for Strongyle group. On age wise analysis, it was revealed that the prevalence of helminth was maximum (46.39%) in young age group; followed by adult (27.83%) and old animals (25.77%). On season wise analysis, it was observed that the rainy season (51.54%) has highest prevalence followed by winter (34.02%) and summer (14.43%).